1998
DOI: 10.1038/sj.leu.2401035
|View full text |Cite
|
Sign up to set email alerts
|

The modulating effect of PSC 833, cyclosporin A, verapamil and genistein on in vitro cytotoxicity and intracellular content of daunorubicin in childhood acute lymphoblastic leukemia

Abstract: Resistance to anthracyclines is related to a poor prognosis in childhood acute lymphoblastic leukemia (ALL). Resistance to this class of drugs may (partly) be reversed by modulating agents, as has been demonstrated in a variety of cell lines. However, it is unknown which modulators may be of clinical benefit in childhood ALL. Therefore, we studied the modulating effect of PSC 833, cyclosporin A (CsA), verapamil (Vp) and genistein on daunorubicin (DNR) cytotoxicity, accumulation and retention in childhood ALL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Inhibiting P-gp function with diverse pharmacological agents circumvents the MDR phenotype. Compounds such as verapamil, cyclosporine, and certain kinds of flavonoids were reported to sensitize MDR cells to cytotoxic agents (3)(4)(5). Rhodamine 123 (Rh123) has been observed to accumulate in the mitochondria of cells and is used as a standard functional indicator of MDR (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting P-gp function with diverse pharmacological agents circumvents the MDR phenotype. Compounds such as verapamil, cyclosporine, and certain kinds of flavonoids were reported to sensitize MDR cells to cytotoxic agents (3)(4)(5). Rhodamine 123 (Rh123) has been observed to accumulate in the mitochondria of cells and is used as a standard functional indicator of MDR (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that the expression of MRP did not correlate with resistance to DNR and the intracellular accumulated DNR concentration in a large series of childhood ALL (Den Boer et al , 1997a, b; 1998b). Moreover, accumulation deficits could not be reversed by P‐gp and/or MRP modulators such as PSC 833, cyclosporin A, verapamil and genistein (Den Boer et al , 1998a). Therefore our data do not directly support the hypothesis that drug resistance in childhood ALL is due to MRP‐mediated transport of (glutathione‐conjugated) drugs out of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…To prevail over the adverse side effects of first-generation inhibitors, researchers modified their structures and these inhibitors, known as second-generation P-gp inhibitors, were developed including dexverapamil, S9788, and PSC-833 also called valspodar (cyclosporine A analog), etc. The second-generation P-gp inhibitors often caused interference with anticancer drugs and affected their pharmacokinetics, resulting in adverse side effects [ 37 , 38 ]. The third generation of inhibitors such as elacridar, zosuquidar and tariquidar were subsequently tested in clinical studies but also failed to achieve clinical approval due to severe cytotoxic side effects [ 39 , 40 ].…”
Section: Mechanisms Associated With Mdr In Cancermentioning
confidence: 99%